Oral Frailty as a Risk Factor for Physical Frailty and Mortality in Community-Dwelling Elderly. (17th November 2017) - Tanaka, Tomoki; Takahashi, Kyo; Hirano, Hirohiko; Kikutani, Takeshi; Watanabe, Yutaka; Ohara, Yuki; Furuya, Hiroyasu; Tetsuo, Tsuji; Akishita, Masahiro; Iijima, Katsuya
Abstract: Background: Oral health is important for maintaining general health among the elderly. However, a longitudinal association between poor oral health and general health has not been reported. We investigated whether poor oral status can predict physical weakening (physical frailty, sarcopenia, and subsequent disability) and identified the longitudinal impact of the accumulated poor oral health (i.e. oral frailty) on adverse health outcomes, including mortality. Methods: A total of 2, 011 elderly individuals (aged ≥ 65 years) participated in the baseline survey of the Kashiwa study in 2012. At baseline, 16 oral status measures and covariates such as demographic characteristics were assessed. As outcomes, physical frailty and sarcopenia were assessed at baseline and at follow-up in 2013 and 2014. Physical independence and survival were assessed from 2012 to 2016 at the time of long-term care certification and time of death. Results: Poor oral status as determined by the number of natural teeth, chewing ability, articulatory oral motor skill, tongue pressure, and subjective difficulties in eating and swallowing significantly predicted future physical weakening (new onsets of physical frailty, sarcopenia, and disability). Oral frailty was defined as co-existing poor status in ≥3 of the six measures. Sixteen per cent of participants had oral frailty at baseline, which was significantly associated with 2.4-, 2.2-, 2.3-, and 2.2-fold increased risk of physical frailty, sarcopenia, disability, and mortality, respectively. Conclusion: Accumulated poor oral status strongly predicted the onset of adverse health outcomes, including mortality among the community-dwelling elderly. Prevention of oral frailty at an earlier stage is essential for healthy aging.